The Process of Implementing The Integrated Dynamic Archiving System (Srikandi) Program in The East Belitung Regency Government - Maryono; Elu, Wilfridus B.; Wulandari, Florentina Ratih (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research is motivated by the Electronic-Based Government System (SPBE) policy in Presidential Decree 95 of 2018. Among the applications mandated, the Indonesian Ministry of PAN RB established the General Application for Dynamic Archiving (AUBKD), named the Integrated Dynamic Archiving Implementation System (SRIKANDI), through the Decree of the Minister of PAN RB number 679 of 2020. SRIKANDI is mandated for implementation in government agencies, regional governments, BUMN/D, and universities across Indonesia. SRIKANDI, derived from Presidential Decree 95 of 2018, has elicited varied responses from these entities, especially those with existing archiving applications and significant investments. Some agencies have not adopted SRIKANDI due to their established systems, while others, like East Belitung Regency, lacking an archiving application, chose SRIKANDI. This study employs a qualitative approach with descriptive analysis to explore the implementation process of the SRIKANDI program in East Belitung. The goal is to describe the implementation using the Van Meter and Van Horn models. Findings indicate that implementation and communication activities between organizations, internally within East Belitung Regency and externally with the government, were conducted directly. However, the results were suboptimal, highlighting the need for improved communication planning for effectiveness. The East Belitung Regency government, including the designated implementation team, did not fully grasp the broader context of the SRIKANDI program, focusing instead on distributing the application to regional ASN. This misalignment with the program's context, intent, and objectives, along with insufficient supervision, led to less-than-optimal results. Economic, social, and political conditions impacting the SRIKANDI program had a positive but insufficiently budgeted influence. The program's disposition shows that the implementation stages are clear, as evidenced by the SRIKANDI action plan document. Implementing resources have been enhanced, particularly in using the SRIKANDI application, through training by ANRI and the East Belitung Regency team.